Liveworksheet-based e-LKPD: an evaluation of a workshop aiming to improve Social studies teachers' pedagogical competence - Wiradimadja, Agung; Saraswati, Dewi; Ruja, I Nyoman; Wahyuningtyas, Neni; Ratnawati, Nurul (Universitas Negeri Malang, 2023)
Teachers often present monotonous teaching and learning processes and use conventional assignments through LKPD (student worksheets) during a pandemic. The manual assessments take time and effort. Departing from that problem, UM Social Sciences Education Lecturer Team organized a workshop on liveworksheet-based e-LKPD (electronic LKPD) as a form of community service. This Program aims to improve the pedagogic competence of teachers. A series of activities have been carried out, and evaluation actions are needed in this workshop activity. The purpose of writing this article is to evaluate the workshop using the CIPP evaluation model, namely context evaluation, input evaluation, process evaluation, and product evaluation. The results of data analysis using CIPP show that the percentage value of the evaluation of the Liveworksheet-based E-LKPD Workshop for improving the pedagogic competence of Social Science teachers in Malang is Very Good. This value indicates that the implementation of the community service that has been carried out has a very well-implemented system.